FIRST FACTS about the VIKINGS - PENNY CU\RKE (scholastik, 1996)
lKIf'GS spent all their Ume raiding. and looUng and they killed anyone: who gOlln their way. right? That's the Idea most people have of them. but Is It true? Why did so many of them leave their homes to cross rough seas In small boats? Their ancestors had lived for centuries In the lands we call Scandinavia: Norway. Sweden and Denmark. They were farmers. flshemlcn and traders. By the 8th century they were moving lnto other lands around the Baltic Sea. But the rest of Europe Ignored the VIkings unU] the 9th century, when boatloads of raiders began to attack the coasts of Britain, Ireland, France, Spain and the Mediterranean. They settled In Iceland ., - J and Greenland. A few even reached America. For 300 years. from about 790 to 1100 the Vikings raided. traded and explored further than any Europeans before them. It took courage. or desperation, to sail out of Sight of land across the AtlanUc - no other sailors would attempt this unUI Christopher Columbus in 1492.